PHONOLOGICAL CORRELATES OF SOCIO-ECONOMIC BACKGROUND OF ENGLISH SPEECH OF SECONDARY SCHOOL STUDENTS IN OYO AND OGUN STATES, NIGERIA (2017)
Phonological correlates of the socio-economic background of the English speech of secondary school students describe the extent to which pronunciation skills have linear relationship with the economic status of their families. Existing literature on the Nigerian English (NE) pronunciation has concentrated on the varieties of adult speakers of NE, using educational attainment as a parameter. There is a dearth of studies on the speeches of Nigerian youths to validate the existence of correlation between socio-economic background and pronunciation skills. This study, therefore, examined the English speeches of 400 selected senior secondary school students in Oyo and Ogun states to investigate a relationship between their socio-economic background (school fees, parents’ income and social status) and their articulation of salient English segmentals and suprasegmentals. William Labov’s Variability Concept and Prince and Liberman’s Metrical Phonology were adopted to analyse socio-economic variables and determine syllable weight respectively. One each of high-fee-paying private school (HFPPS) and state-owned tuition-free public school (PS) were purposively selected from Oyo and Ogun states. One hundred senior secondary school students from each of the four schools were randomly selected. A Socio-Economic Background Scale was administered to determine socio-economic status of the selected students’ families. Participants produced validated Phonological Correlate Test sentences and a passage into speech filing system. Quantitative data were analysed and subjected to descriptive and t-test statistics at 0.05 level of significance, while qualitative data were subjected to metrical analysis. There was a significant difference between socio-economic background of HFPPS and PS based on school fees, parents’ income and social status (t(398) = 4.254). The HFPPS (x ̅=22.0) performed better than PS (x ̅=1.4) in differentiating long and short vowels /I, i:/, /æ, a:/, /ɒ, ɔː/, /ʊ, u:/ (t(398) = 44.384). The PS (x ̅=0.7) monophthongised closing diphthongs and substituted sounds from indigenous languages for centring diphthongs, while HFPPS (x ̅=10.9) approximated to Received Pronunciation (RP) (t(398) = 42.965). The HFPPS (x ̅=30.6) produced the dental fricatives /Ɵ, ð/ appropriately, while PS (x ̅=5.6) did not (t(398) = 35.280). The HFPPS (x ̅=30.6) produced the voiced palato-alveolar fricative /Ʒ/, better than PS (x ̅=5.6), (t(398) = 35.280). The HFPPS (x ̅=9.4) did not manifest h-dropping, while PS (x ̅=0.4) did (t(398) = 55.62). For suprasegmentals HFPPS (x ̅=5.8) approximated to RP in the application of the phonetic cues to stress, while PS (x ̅=0.3) did not (t(398) = 30.155). The HFPPS (x ̅=15.3) performed better in the assignment of intonation tunes than PS (x ̅=2.8), (t(398) = 35.280). The HFPPS alternated (S)trong and (W)eak syllables, approximating to RP; while the PS’ production was characterised by (S)trong syllables and stress clashes. Students’ socio-economic background positively correlated with their articulation of salient English segmentals and suprasegmentals in high-fee-paying private and state-owned tuition-free public schools in Oyo and Ogun states, Nigeria. However, the high-fee-paying private school students approximated to Received Pronunciation, while the public school students deviated remarkably.